Penguatan Pemahaman dan Persepsi Positif Perawat dalam Melaksanakan Dokumentasi Asuhan Keperawatan sebagai Upaya Meningkatkan Mutu Layanan Kesehatan di Rumah Sakit - Heryyanoor Heryyanoor; Melinda Restu Pertiwi; Diana Hardiyanti (Poltekkes Kemenkes Surakarta, 2024)
Background: Problems related to the documentation of nursing care are still a global problem in hospitals. Various factors, such as knowledge, attitudes, skills, and different perceptions between nurses when carrying out nursing documentation, also become obstacles. Methods: The design applied in the service refers to qualitative discrimination, with activities carried out to socialize research results, followed by FGD (Focus Group Discussion) with an interview guide consisting of nine statements to 10 nurses representing the treatment room as participants. Results: There was a change in understanding and shared positive perceptions among participants regarding the implementation of nursing documentation, starting with assessment, data analysis, formulation of nursing diagnoses, and evaluation. Conclusion: increasing nurses' understanding and positive perceptions regarding nursing documentation can be done through FGDs, training, and workshops, as well as ongoing assessment.